2020
DOI: 10.1007/s42452-020-2415-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of pectin production from dragon fruit peels waste: drying, extraction and characterisation studies

Abstract: Reutilisation of agricultural wastes is a major challenge faced by the research community. The current study aimed to address this issue by recovering commercial pectin from dragon fruit peels by investigating the pretreatment and extraction process and their parameters. Optimum oven-drying temperature was identified at 45 °C with the highest pectin yield (6.27%) and the lowest ash content (8.34%). Investigation of the drying kinetics revealed Page's model as the best-suited model to the experimental data in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…In addition, there was evidence that amylase-catalysed starch hydrolysis may be affected due to the interaction between pectin and amylase [43]. Polygalacturonic acid, a pectin component of pitaya peel [44], might interact electrostatically with α-amylase and act as a non-competitive inhibitor of this enzyme [45]. Moreover, cookies incorporated with high PPP ratios contained more phenolic compounds which might reduce their glycemic index by the inhibition of α-amylase and/or α-glucosidase as well as the interactions between polyphenol and starch molecules [46].…”
Section: Effects Of Pitaya Peel Powder Levels On Predicted Glycemic I...mentioning
confidence: 99%
“…In addition, there was evidence that amylase-catalysed starch hydrolysis may be affected due to the interaction between pectin and amylase [43]. Polygalacturonic acid, a pectin component of pitaya peel [44], might interact electrostatically with α-amylase and act as a non-competitive inhibitor of this enzyme [45]. Moreover, cookies incorporated with high PPP ratios contained more phenolic compounds which might reduce their glycemic index by the inhibition of α-amylase and/or α-glucosidase as well as the interactions between polyphenol and starch molecules [46].…”
Section: Effects Of Pitaya Peel Powder Levels On Predicted Glycemic I...mentioning
confidence: 99%
“…The extraction was carried out utilizing Chua [17], with modification in all runs, and 40 gm of the powdered sample was blended with pH of (2 3) citric acid solution in a 400 mL flask. It was then sonicated for (15 30min), in the range of 60 140W, ultrasound power, thereafter the mixture was maintained at a temperature of 25 0 C and percolated.…”
Section: Pectin Extraction Processmentioning
confidence: 99%
“…The esterification degree was decided based on the procedure adopted by Chua [17], with modification by utilizing Eq. ( 8).…”
Section: Esterification Degree (Ed)mentioning
confidence: 99%
“…The DE of high methoxyl pectin (HMP) is higher than 50%, and that of low methoxyl pectin (LMP) is <50% (Duan et al, 2021). Currently, commercial pectin is mostly derived from apple pomace and citrus peel (Zhong et al, 2021); however, many other plants are reported to be good sources of pectin, including pomelo peel, sugar beets, and dragon fruit (Guo et al, 2016; Kazemi et al, 2019; Chua et al, 2020; Tocmo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%